Applying classification controls to Internet content in Australia. Issue 2 (11th May 2015) - Leitch, Shona; Warren, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to explore Australian public and stakeholders views towards the regulation of the Internet and its content. The federal government called for submissions addressing their proposal, and this paper analyses these submissions for themes and provides clarity as to the Australian public and stakeholders key concerns in regards to the proposed policy. Design/methodology/approach – The paper uses a qualitative approach to analyse the public consultations to the Australian Federal Government. These documents are coded and analysed to determine negative and positive viewpoints. Findings – The research has shown, based upon the analysis of the consultation, that there was no public support for any of the measures put forward, that the Australian Federal Government in its response has not recognised this public feedback and instead has only utilised some of the qualitative feedback obtained through the public consultation process to try to justify its case to proceed with its proposals. Research limitations/implications – The study is focussed on Australia. Practical implications – The paper analyses a proposed national approach to filtering the content of the Internet and discussed the public reaction to such an approach. Social implications – The paper looks at how different parts of Australian society view Internet filtering in a positive or negative manner. Originality/value – The only study that directly looks at the viewpoint of the Australian public.